2011
DOI: 10.1016/j.schres.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Application of systems biology approach identifies and validates GRB2 as a risk gene for schizophrenia in the Irish Case Control Study of Schizophrenia (ICCSS) sample

Abstract: Recently, we prioritized 160 schizophrenia candidate genes (SZGenes) by integrating multiple lines of evidence and subsequently identified twenty-four pathways in which these 160 genes are overrepresented. Among them, four neurotransmitter-related pathways were top ranked. In this study, we extended our previous pathway analysis by applying a systems biology approach to identifying candidate genes for schizophrenia. We constructed protein-protein interaction subnetworks for four neurotransmitter-related pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 38 publications
(45 reference statements)
2
18
0
Order By: Relevance
“…However, the number of grooming is increased in a statistically considerable scale. Similar results is provided that a decrease in the motor activity is argued in [25][26].…”
Section: Discussionsupporting
confidence: 80%
“…However, the number of grooming is increased in a statistically considerable scale. Similar results is provided that a decrease in the motor activity is argued in [25][26].…”
Section: Discussionsupporting
confidence: 80%
“…GWAS data on Crohn's disease (Akula et al, 2011), as well as to analyze e.g. sets of candidate genes for schizophrenia (Jia et al, 2012;Sun et al, 2011) and major depressive disorder (Deo et al, 2013;Jia et al, 2011a). Networks can associate many different genes with the same biological functionality by "guilt-by-association" , and represent an interesting future avenue to develop and apply further for analysis of GWAS data on e.g.…”
Section: Pathway / Network Gwasmentioning
confidence: 99%
“…In paranoid SCZ, GRB2 was hypermethylated in intron. GRB2 gene was annotated with GO terms axon guidance and nerve growth factor receptor signaling pathway and recently reported as a risk gene for SCZ in the Irish population [Sun et al, 2011]. As another member of nerve growth factor receptor signaling pathway, PRKCA gene variants was found to be associated with lower memory test scores and increased risk of SCZ [Jablensky et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…For example, as a susceptible gene for SCZ [Chen et al, 2011], DISC1 was detected with aberrant DNA methylation both in paranoid and undifferentiated SCZ. In addition, there were other candidate genes such as such as GRB2 [Sun et al, 2011], PRKCA [Jablensky et al, 2011], DLG4 [Cheng et al, 2010] found with aberrant DNA methylation in paranoid SCZ, and XRCC4 in undifferentiated SCZ. These results indicate that both the genetic and epigenetic factors are the major causes of SCZ.…”
Section: Neuron System Related Genes Were Enriched In the Hypermethylmentioning
confidence: 99%